Primary augmentation mammoplasty in a plastic surgery residency service - Neto, Balduino Ferreira De Menezes; Secanho, Murilo Sgarbi; Carvalho, Laisa Brandão; Moragas, Weber Ribolli; Palhares, Aristides Augusto (Thieme, 2021)
Introduction: Primary augmentation mammoplasty is one of the main cosmetic surgeries in the plastic surgeon’s routine. The various performance techniques require constant study and extensive training of the specialty’s resident physicians. Methods: Review medical records of patients who underwent primary augmentation mammoplasty at the Hospital das Clínicas of the Faculdade de Medicina de Botucatu from 2017 to 2020. Results: 120 surgeries were performed during the period analyzed. There was a predominance of high-projection (75%) and subfascial (67.5%) implants. There were no major complications, with most patients (75%) not having any minor complications (p<0.001). Conclusion: Augmentation mammoplasty is a safe surgery when performed following proper technical care and under supervision.
Mastoplastia de aumento primária em serviço de residência médica de cirurgia plástica
Keywords: Breast implant; Breast implants; Internship and residency; Mammoplasty; Plastic surgery; Teaching Hospitals